2009
DOI: 10.1016/j.chembiol.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Small Molecule Inhibitor of Formin-Mediated Actin Assembly

Abstract: SUMMARY Formins stimulate actin filament assembly for fundamental cellular processes including division, adhesion, establishing polarity and motility. A formin inhibitor would be useful because most cells express multiple formins whose functions are not known, and because metastatic tumor formation depends upon the deregulation of formin-dependent processes. We identified a general small molecule inhibitor of formin homology 2 domains (SMIFH2) by screening compounds for the ability to prevent formin-mediated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
353
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(410 citation statements)
references
References 50 publications
21
353
1
Order By: Relevance
“…We further examined this main defect, which might be related to contractile ring formation and thus straight actin nucleators (Barr and Gruneberg, 2007;Fededa and Gerlich, 2012). To determine whether formin proteins are involved in cleavage furrow closure during PBE, oocytes were treated with 100 mM SMIFH2, a specific inhibitor of the formin homology (FH) 2 domain (Rizvi et al, 2009). To avoid perturbation of GVBD and to ensure correct spindle formation, SMIFH2 treatment was performed after GVBD (30 minutes after the treatment with 1-MeAde).…”
Section: Resultsmentioning
confidence: 99%
“…We further examined this main defect, which might be related to contractile ring formation and thus straight actin nucleators (Barr and Gruneberg, 2007;Fededa and Gerlich, 2012). To determine whether formin proteins are involved in cleavage furrow closure during PBE, oocytes were treated with 100 mM SMIFH2, a specific inhibitor of the formin homology (FH) 2 domain (Rizvi et al, 2009). To avoid perturbation of GVBD and to ensure correct spindle formation, SMIFH2 treatment was performed after GVBD (30 minutes after the treatment with 1-MeAde).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a recent study showed that NMII-rich actin arcs in the IS are derived from formin-mediated actin polymerization primarily in the lamellipodia (51). To test whether the activation of ROCK and formin mediates MT-actin interactions at the T-cell contact zone, we activated EB3-EGFP-and TagRFP-Tactin-expressing Jurkat cells on anti-CD3-coated coverslips in the presence of Y-27632 or the formin inhibitor SMIFH2 (15 μM) (52). SMIFH2 inhibits the actin polymerization activity of formins.…”
Section: Mt Network Forms a Radially Emanating Dynamic Array During Tmentioning
confidence: 99%
“…Rizvi, et al [26] recorded high mortality on Indian mustard followed by yellow sarson, gobhi sarson and cauliflower in all life stages of P. brassicae due to difference in nutritional values of host plants. The maximum survival fractions were recorded at later stage of development on cabbage as compared to other cole crops [27].…”
Section: Discussionmentioning
confidence: 99%